Litzmannstadt – nazistowski eksperyment narodowościowy na ziemiach polskich - Siepracka, Dorota; Wróbel, Janusz (Pamięć i Sprawiedliwość, 2008)
In 1937 Łódź was the second biggest city in the Republic of Poland with approximately 653 000 inhabitants, with Warsaw being the biggest one. Although Poles constituted the majority of inhabitants, Jews and Germans formed not only numerous but also economically affluent ethnic minorities. Łódź as one of the biggest cities in Eastern and Central Europe and at the same time one of the main centers of the German minority in Poland for a long time was of interest of the Reich. This interest increased especially after Hitler had taken over the power in 1933 and it stemmed from the fact that the Reich considered demographic issues important. The Nazifi cation of the German minority in Poland including the one in Łódź, supported and inspired by the Reich, made it easier for Hitler to plan the changes in the ethnic relations in Eastern and Central Europe after the victorious war with Poland in 1939. Poles and Jews were to be removed from Łódź to central Poland and they were to be replaced with Germans. That way the Nazi authorities wanted to transform Łódź into the city with the German majority. It was a great experiment of the Nazi ethnic policy as a result of which the deep demographic changes unprecedented in the history of Łódź took place. First of all, the general demographic potential of the city was seriously reduced. Although, the occupier signifi cantly enlarged the territory of the city at the end of 1944 the general number of the inhabitants amounted to 486 000 that is as much as 186 000 less than before the outbreak of the War within the pre-war city borders. If we take into consideration the territory of the occupation-time Łódź, the general decline in the number of inhabitants was much larger – by as much as 290 000. The number of domineering Polish inhabitants decreased from 452 000 in 1939 to 342 000 in May 1944; the decrease thus amounted to 110 000. The Jewish inhabitants of the city were nearly totally removed. The only ethnic group whose demographic potential increased signifi cantly was the Germans. Deep and irreversible demographic changes in Łódź, however, cannot be perceived as the success of the Nazi ethnic policy. The ethnic experiment which lasted here from the autumn of 1939 ended in the winter of 1945 in the manner completely unexpected by the Nazi. As a result of the hasty evacuation in the wake of the approaching front about 35 000 people of German nationality remained in the city that is half of the number of Germans before the WWII.